Psychosis risk stigma and help‐seeking: Attitudes of Chinese and Taiwanese residing in the United States. Issue 1 (24th May 2019) - He, Emily; Eldeeb, Sherief Y.; Cardemil, Esteban V.; Yang, Lawrence H.
Abstract: Aim: Intervention during the clinical high‐risk phase for psychosis (CHR) can reduce duration of untreated psychosis and associated negative outcomes. Early treatment access and sustained engagement are important to understand for effective intervention. Understanding stigma and help‐seeking processes is particularly important for groups that experience mental healthcare disparities such as those of Chinese heritage living in the United States. Methods: Chinese and Taiwanese participants (N = 215) residing in the United States were randomly assigned to one of three CHR vignette conditions based on the "what matters most" stigma framework for Chinese groups, which identifies capacities that define "personhood" and thereby shapes stigma for members of a particular cultural group. Participants completed measures of help‐seeking attitudes, family stigma and individual stigma. Results: More stigma towards the CHR vignette character's family was associated with positive CHR help‐seeking attitudes. Participants who read the vignette describing CHR affecting family obligations, "what matters most" and participants who read the vignette describing CHR symptomology only had more positive CHR help‐seeking attitudes compared to participants who read the vignette describing CHR affecting individual aspirations. Conclusions: Chinese and Taiwanese residing in the United States may perceive professional mental healthcare to be especially relevant for persons with CHR when symptoms are particularly stigmatizing for the person's family and when symptoms threaten the person's ability to fulfil family obligations (ie, "what matters most"). Clinical implications of findings include the importance of emphasizing positive treatment outcomes that increase an individual's ability to engage in valued life domains.